The Strategy of Islamic Tourism Development in West Java - Abdurrahman MBP (JURNAL ALAMIAH, 2020)
Sharia Tourism is a term used by the Ministry of Tourism and Creative Economy, Republic of Indonesia, to the tour program based on the values of the Islamic sharia. The program was launched in December 2012 as the implementation of Law no. 10 of 2009 concerning about tourism, that tourism was organized by upholding the principle of religious norms and cultural values of the nation. West Java as one of the sharia-tourist destinations has rich tourism potential that can be developed with the values of Islamic sharia. Among these attractions are the Kampung Dukuh and Kampung Naga, Tasikmalaya. The tourism potentials that exist in these both locations are tourism of nature, local traditions, pilgrimage tourism, traditional art, and historical tours. However, initial observations that researcher did, indicated these potentials did not yet discover optimally. The apropriate strategies are needed to develope the sharia tourism in these both Kampung Dukuh and Kampung Naga. This research will formulate the strategy of sharia-based tourism development in Kampung Dukuh and Kampung Naga. The goal is to identify the potential of tourism there, analyzing internal and external environment, and determine the development strategy of both traditional village as a sharia tourist attraction. The data in this study were obtained through the method of participant observation, in-depth interviews and documentation. This study is explorative; formulate programs based on internal conditions and external conditions in both sites. The results showed that the strength of Sharia tour in Kampung Dukuh and Kampung Naga include the value of the local community and religious ritual, pilgrimage tourism, unique architecture, natural beauty that lies in the mountainous region, good roads, easy access (to Kampung Naga), and the strategic position. While the weakness of Kampung Dukuh and Kampung Naga include lack of hygiene and environmental sustainability, lack of availability of tourist transport (to Kampung Dukuh), the lack of tourism facilities, the lack of parking space, still lack of toilet facilities for public, unavaillable manager of the attraction, unmaximum promotional efforts, and the unavailability of Tourist Information Center. Based on the analysis of these strengths and weaknesses, I formulate four development strategies that can be applied, namely product development strategy, promotion strategy development, sustainable tourism strategy, and the strategy of human resource development (HRD) based on the values of the Islamic Sharia.